Perancangan Sistem Informasi Tender Bokar Menggunakan Metode Design Thinking - Letty Latifani Arifah; Allsela Meiriza; Pacu Putra; Nabila Rizky Oktadini; Putri Eka Sevtiyuni (STMIK Budi Darma, 2023)
The government has been established improving the quality of rubber by implementing the Gerakan Nasional Bokar Bersih directed through Unit Pengolahan dan Pemasaran Bokar or UPPB. In processing and marketing rubber, UPPB conducts a rubber tender system. One of the UPPBs that applies the rubber tender system is UPPB KT. Karya Tani-IV. However, the tender system is still carried out conventionally through the Whatsapp group, so that the marketing of rubber carried out is still less extensive and is only marketed to known tender participants. In addition, UPPB KT. Karya Tani-IV currently does not have a website-based information system that can store farmer rubber recording data using a database. Therefore, this research provides a solution to design a prototype of the rubber tender Information System using the Design Thinking method. The design thinking method is considered capable of overcoming the problems faced by creating solutions based on user needs. The Design Thinking method is used to solve problems through creative ways by involving users into thinking activities and the user's point of view is used as the main benchmark in an action or activity in solving problems. The prototype of this system is designed to expand the reach of rubber marketing and make it easier for UPPB KT. Karya Tani-IV in processing rubber data. After testing the prototype using the System Usability Scale method, a final score of 82.45 was obtained. The final score obtained is included in the Acceptability Ranges category of